Correlation of Ischemic Time with Diastolic Dysfunction and Correlation of Diastolic Dysfunction with 6 Minute Walk Test Distance in STEMI Patients Receiving Percutaneus Coronary Intervention - Imelda Krisnasari; Anna Fuji Rahimah; Mohammad Saifur Rohman; Setyasih Anjarwani; Indra Prasetya (Heart Science Journal, 2022)
Background: Minimizing the time between ischemia and reperfusion in STEMI patients is critical for salvaging ischemic myocardium and limiting residual injury. One of the methods for determining the impact of ischemic time on the myocardium and correlating the findings to the outcomes is by using echocardiography.Objectives: To evaluate the correlation of ischemic time to diastolic dysfunction and also the correlation of diastolic dysfunction to functional capacity by 6-minute walk distance in STEMI patients. Methods: The study was a retrospective cohort, with all STEMI patients who underwent PCI at RSUD Dr. Saiful Anwar Malang between January 2018 and November 2021 being eligible. All patients underwent PCI, echocardiography, and a 6-minute walk test before being discharged. We defined significant diastolic dysfunction as grade 2 or 3 diastolic dysfunction, according to the 2016 American Society of Echocardiography (ASE) and European Association of Cardiovascular Imaging (EACVI) guidelines. The distance of 6-minute walk test was divided into three categories: less than 300m, 300-400m, and more than 400m.Results: From total 258 patients, 92 patients (35.7%) had significant diastolic dysfunction. The significant diastolic dysfunction was correlated with ischemic time > 12 hours (r = 0.51, p = 0.000), Killip class (r= 0.46, p = 0.000), culprit artery (r= 0.203, p=0,001), and peak toponin I levels (r=0.35, p=0.000). We identified that the ischemic time (odds ratio / OR 6.78; 95% Confidence Interval / CI 3.27 – 14.09; p  = 0.000), Killip class (odds ratio 4.62, 95% CI 2.53 to 8.48, p = 0.000), and infarct size by peak troponin I levels (OR 1.12, 95% CI 1.06 to 1.18, p  = 0.000) as independent predictors of significant diastolic dysfunction. There was inversely correlation of diastolic dysfunction with 6-minute walk test distance. (r = -0,422 dan p=0,000), with E/e’ as independent predictors of level of 6 minute walk distance (OR -1.126, 95% CI -1.78 to -0.48, p = 0.001).Conclusion: Ischemic time is one of the independent predictors of significant diastolic dysfunction. LV diastolic dysfunction was inversely correlated with 6-minute walk test distance in STEMI patient.